2021
DOI: 10.1002/pbc.29411
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal mycobiota composition and changes in children with thalassemia who underwent allogeneic hematopoietic stem cell transplantation

Abstract: Background: Allogeneic hematopoietic stem cell transplantation (HSCT) alters the diversity of the intestinal bacterial microbiota. This study aimed to evaluate human mycobiota composition pre-HSCT and post-HSCT in children with thalassemia.Method: Ten children with thalassemia undergoing allogeneic HSCT were enrolled.The stool samples were collected before the transplantation regimen, before the transplant day, and +15, +30 days, and three months after transplantation. Stool samples were also collected from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…In this study, the Shannon index was low and similar between patients before transplantation but significantly lower on days 15 and 30 after transplantation. 19 Another study found that HSCT resulted in a profound disturbance of the gut ecosystem, measured by the loss of about 30% of the pre-HSCT alpha diversity. Additionally, the mean value of weighted UniFrac distances among pre-HSCT samples was significantly lower than post-HSCT samples, demonstrating the increased inter-subject gut microbiota diversity after transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the Shannon index was low and similar between patients before transplantation but significantly lower on days 15 and 30 after transplantation. 19 Another study found that HSCT resulted in a profound disturbance of the gut ecosystem, measured by the loss of about 30% of the pre-HSCT alpha diversity. Additionally, the mean value of weighted UniFrac distances among pre-HSCT samples was significantly lower than post-HSCT samples, demonstrating the increased inter-subject gut microbiota diversity after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing evidence has indicated that posttransplant microbiota deviation is closely associated with allo-HSCT outcomes, including infectious complications, graft-versus-host disease (GVHD), disease relapse, and mortality. 7 Previous studies have demonstrated the role of gut microbiota in metabolic, cardiovascular, and mental diseases. 8 However, little research on hematological diseases is available, especially in pediatric patients.…”
mentioning
confidence: 99%
“…The mycobiome has also been investigated in the context of HSCT. In a first-of-its-kind proof-of-concept study, a metagenomic analysis of the gut mycobiota composition of ten children with thalassemia undergoing allogeneic HSCT was done at four different time points (transplant day, 15 days post-transplant, 30 days post-transplant, and 90 days post-transplant) to evaluate how HSCT impacts the diversity of the human gut mycobiota ( 106 ). No notable changes in the gut mycobiome were observed up to a month following transplantation, and the dominating phylum was Ascomycota .…”
Section: Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%
“…However, more focused future investigations into the relationship of Malassezia spp. and GVHD in HSCT patients may help in the development of novel microbial biomarkers as well as targeted therapeutic interventions involving this genus ( 106 ). Although the bacteriome, virome, and mycobiome individually provide interesting insights with potential clinical relevance, a siloed understanding of these individual biomes may not be representative of the community dynamics at play.…”
Section: Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%
“…The vast majority of microbiome studies were performed using ribosomal DNA (rDNA) based sequencing methods designed for bacterial and fungal 16/23S, 18/28S or ITS region rDNA sequences, respectively, thus neglecting the archaeome, non-fungal eukaryome, and the DNA virome (Borrel et al 2020, Kurilshikov et al 2021, Richard and Sokol 2019, Sen and Thummer 2022, Stockdale and Hill 2021, Vandeputte et al 2017, Yalcin et al 2022, Zhernakova et al 2016). rDNA sequencing is a well-established, scalable, and cost-effective technology; it has, however, important limitations as it bears potential amplification-induced biases in bacteriome/mycobiome composition estimates and challenges in reliably assigning accurate species - or genus-level labels (Edgar 2018).…”
Section: Introductionmentioning
confidence: 99%